Scenario modeling of Information and Political Threats in the Internet - V. V. Borshchenko (Евразийская интеграция: экономика, право, политика, 2020)
The article deals with information threats concerning the influence of different political manipulation methods, affecting the social development of the country. The theory of scenarios presented in the article allows to evaluate possible alternatives to their implementation in the Internet space. The scenario forecasting method for information and political threats is proved.